2015
DOI: 10.3109/0886022x.2015.1120097
|View full text |Cite
|
Sign up to set email alerts
|

A review of the impact of oxidative stress and some antioxidant therapies on renal damage

Abstract: An increase in the generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) leads to complications during chronic kidney disease (CKD). This increase essentially derives from the impairment of natural antioxidant systems of the organism. The resulting oxidative stress produces damage to kidney tissue, especially by affecting nephrons and more generally by disrupting the function and structure of the glomerulus and interstitial tubule. This leads to a rapid decline in the condition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Also, some studies have reported the association of low-level Cd exposure with decreased eGFR, supporting the hypothesis that trace exposure to Cd may contribute to the development of CKD ( Åkesson et al , 2014 ; Ferraro et al , 2010 ). There are also studies suggesting that oxidative stress is also involved in the onset of CKD ( Tamay-Cach et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, some studies have reported the association of low-level Cd exposure with decreased eGFR, supporting the hypothesis that trace exposure to Cd may contribute to the development of CKD ( Åkesson et al , 2014 ; Ferraro et al , 2010 ). There are also studies suggesting that oxidative stress is also involved in the onset of CKD ( Tamay-Cach et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake of antioxidants has been associated with reduced risks of some of the aforementioned diseases [6,7]. The effectiveness of antioxidant therapies in preventing and/or managing human pathologies was also highlighted [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also compared the patients' cognitive status with a control group using the MMSE; in this study, however, since the aim was to determine the effect of CoQ10 supplement on dialysis patients' cognitive status, the MMSE scores of the supplement group were not compared with a non-dialysis control group, rather, the changes in the cognitive status of hemodialysis patients under the effect of CoQ10 supplement were compared with a hemodialysis group that did not receive this supplement. Previous studies have also addressed the effect of CoQ10 supplementation in preventing the progress of renal disease and have reported positive effects for this supplement (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%